Programming a Cochlear Implant for Tinnitus Suppression - Perreau, Ann; Tyler, Richard; Mancini, Patricia C. (Journal of the American Academy of Audiology, 2020)
Background Electrical stimulation of the cochlea to treat tinnitus has been explored for decades. However, few studies have investigated the most salient programming parameters for tinnitus suppression in cochlear implant (CI) patients.Purpose The purpose of this study was to review the available CI programming parameters for tinnitus suppression and to consider possible clinical research designs for selecting the optimal programming parameters for CI patients.Results Across research studies, the optimal parameters vary significantly and are often based on data fromonly a fewparticipants. Electrical stimulation using lowand high rates, different electrode numbers, and low T-levels were helpful in suppressing tinnitus, although more research is needed from a greater number of CI patients. Possible designs for evaluating these parameters in a clinical setting are presented.Conclusions Programming a CI to reduce the prominence of tinnitus is complex, and audiologists should consider adjusting CI parameters systematically for CI patients with bothersome tinnitus.
Keywords: cochlear implants; tinnitus